Lottery versus All-Pay Auction Contests – A Revenue Dominance Theorem - Jörg Franke; Christian Kanzow; Wolfgang Leininger; Alexandra Schwartz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
We allow a contest organizer to bias a contest in a discriminatory way, that is, she can favor specific contestants through the choice of contest success functions in order to maximize total equilibrium effort (resp. revenue). The scope for revenue enhancement through biasing is analyzed and compared for the two predominant contest regimes; i.e. all-pay auctions and lottery contests. Our main result reveals that an appropriately biased all-pay auction revenue dominates the optimally biased lottery contest for all levels of heterogeneity among contestants. Moreover, such a biased all-pay auction will never make use of the celebrated exclusion principle advanced by Baye et al. (1993). – – Wir betrachten einen Contest/Wettstreit-Designer, der durch Wahl einer entsprechenden CSF (contest success function) Wettstreiter gezielt privilegieren oder benachteiligen kann, um die im Wettstreit erbrachte Gesamtanstengung , resp. dessen Gesamtertrag zu maximieren. Es werden die beiden populärsten Wettstreitmodelle betrachtet: Lotterien und All-Pay Auktionen. Unser Hauptresultat zeigt, dass eine vom Designer entsprechend manipulierte All-Pay Auktion immer ertragreicher ist als die ertragreichste manipulierte Lotterie. Dies gilt für beliebig heterogene Wettstreiter. Eine derart manipulierte All-Pay Auktion wird überdies nie vom Exklusionsprinzip' von Baye et al. (1993) Gebrauch machen.
Keywords: C72; D72; 330; All-pay auction; lottery contest; bias; revenue